Estimating farmers' internal value of crop residues in smallholder crop-livestock systems: A South Asia case study. (September 2021) - Olson, Kent; Gauto, Victor; Teufel, Nils; Swain, Braja; Tui, Sabine Homann-Kee; Duncan, Alan; Erenstein, Olaf
Crop residues (CR) are an important, internally produced resource with several uses on smallholder, mixed crop-livestock farms, including livestock feed, mulch, fuel and construction material. This study sets out to develop a method to estimate the internal shadow value of CR as feed and as mulch for smallholder households. The study uses a South Asia case study as illustration using data from a set of village and household surveys in three different sites. The estimated shadow prices were higher for CR as mulch than for CR as feed at all three sites. These results reject the null hypothesis that the estimated shadow price for CR as feed is greater than the shadow price for CR as mulch. Since the null hypothesis was formed based on observing household behavior, the rejection of the null hypothesis implies that there are other reasons to explain why more households use CR as feed versus as mulch.